Pengembangan Media Pembelajaran Interaktif Untuk Materi Pelajaran Pemrograman Dasar Kelas X di SMK Negeri 8 Malang Menggunakan Model APPED - Samsul Arifin; Hanifah Muslimah Az-Zahra; Admaja Dwi Herlambang (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
In the Software Engineering (RPL) class X of SMK Negeri 8 Malang, it can be seen that the learning process is still conventional so students cannot understand basic programming materials, students have difficulty learning independently because they do not have learning resources. So it is necessary to conduct research on Interactive Learning Media Development for Class X Basic Programming Subjects at SMK Negeri 8 MALANG Using the APPED Model. The APPED research model has 5 steps: initial analysis and research, design, production, evaluation and dissemination. The results of ongoing evaluations with three aspect criteria get valid results. At the alpha testing stage the material validator obtained a value of 70.00 in the